2016
DOI: 10.1007/978-3-319-41252-8_5
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Instructional Quality for the Relation Between Achievement in Reading and Mathematics

Abstract: Students gain access to mathematical tasks through reading; consequently, low-performing readers generally perform low in mathematics. High quality instruction might help students develop comprehension strategies for reading mathematics that weakens the relationship between reading and mathematics skills. The main aim of this chapter is to investigate how instructional quality might moderate the relationship between reading and mathematics achievement. Analyzing data from 37 countries and benchmark participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…Paper and pencil tests that assess students' mathematics competence might draw heavily on a student's ability to read and interpret texts. Previous research has demonstrated a high positive correlation between reading comprehension and mathematics achievement (e.g., Nortvedt 2011;Nortvedt et al 2016). The issue of language as a 'gatekeeper' to accessing test content, as well as the consequences of not mastering the language of assessment to a sufficient extent, are also illustrated by the strong negative effect of late arrival (and consequently shorter exposure) to language instruction in the host country (OECD 2015).…”
Section: Equity Issuesmentioning
confidence: 99%
“…Paper and pencil tests that assess students' mathematics competence might draw heavily on a student's ability to read and interpret texts. Previous research has demonstrated a high positive correlation between reading comprehension and mathematics achievement (e.g., Nortvedt 2011;Nortvedt et al 2016). The issue of language as a 'gatekeeper' to accessing test content, as well as the consequences of not mastering the language of assessment to a sufficient extent, are also illustrated by the strong negative effect of late arrival (and consequently shorter exposure) to language instruction in the host country (OECD 2015).…”
Section: Equity Issuesmentioning
confidence: 99%
“…Demir ( 2018) also indicated that the teaching quality components cognitive activation and classroom management increased students' mathematical problem-solving ability. Finally, there is a significant positive correlation between instructional quality and mathematics observed in several, but not all, educational systems (Nortvedt et al, 2016).…”
Section: Teaching Quality and Task Characteristicsmentioning
confidence: 88%
“…However, the reduced ACC in both subtraction and inconsistent sentences might be also due to the differences in the quality of teaching and to false assumptions. False assumptions about WPs (e.g, that every problem can be solved with a single operation; Cummins, Kintsch, Reusser, & Weimer, 1988) are sometimes believed and instructed by teachers (Fuentes, 1998;Nortvedt et al, 2016). In particular, an assumption facilitated and even encouraged by teachers is the use of keyword strategies (e.g., Boote & Boote, 2018;Jitendra et al, 2015).…”
Section: Non-isomorphic Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matematikte başarılı olan öğrencilerin aynı zamanda matematik öğrenmeyi sevmesi, matematiğe değer vermesi, kendilerini okula ait hissetmesi ve akran baskısına çok az maruz kalmaları, ilgili öğrenci özellikleri ile matematik başarısı arasında ilişkilerin bulunduğuna işaret etmektedir. Bu bulgular, önceki araştırmalarda (Doğan ve Barış, 2010;Lee, 2009;Nortvedt (Sharkey ve diğerleri., 2008). Okulunu, öğretmenini ve arkadaşlarını seven öğrencilerin eğitime ilişkin düşüncelerinin ve buna bağlı olarak sergiledikleri çabanın değişim gösterdiği ve bu durumun da matematik başarısı açısından da farklılıklara yol açmış olabileceği düşünülmektedir.…”
unclassified